Adaptive QoS-aware channel access scheme for Cognitive Radio networks. (1st September 2010) - Zhang, Li; Zheng, Guoxin
This paper proposes a three-dimensional traffic model, which can identify and utilise those under-utilised channel opportunities efficiently. Based on this model, an opportunistic channel access scheme, named Adaptive Opportunistic Channel Access (AOCA) schedule algorithm, is presented. It can adaptively schedule channel sensing leveraging the Media Access Control (MAC) layer decisions and maximise channel utilisation without imposing any additional burden on CUs and extra interference on licensed users. Moreover, it can provide cognitive users with Quality of Service (QoS) support. Finally, the simulation results demonstrate that the proposed channel schedule scheme can utilise the channel effectively and flexibly in CR networks.